Legal Analysis of Police Authority in the Implementation of Settlement of Domestic Violence (KDRT) Cases Through the Restorative Justice Approach - Putra, Sanggrayugo Widyajaya; Gunarto, Gunarto (UNISSULA Semarang, 2025)
Abstract. Domestic violence (KDRT) is a criminal act regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. Handling of domestic violence cases must pay attention to the protection of victims, especially women and children. This is reinforced through Perpol Number 8 of 2021 concerning Handling of Criminal Acts Based on Restorative Justice. However, the aplication of restorative justice in domestic violence cases has raised debate regarding the limits of police authority and the potential for neglect of victims' rights. The purpose of the study was to determine and analyze the authority of the police in implementing the resolution of domestic violence crimes through a restorative justice aproach, based on aplicable laws and regulations and to determine and analyze the obstacles and solutions in the aplication of the restorative justice aproach by the police in resolving domestic violence cases. Normative juridical legal research method, namely legal research conducted by examining primary, secondary, and tertiary legal materials as a basis for analyzing legal issues. The police have the authority to implement restorative justice according to Perpol Number 8 of 2021. In cases of domestic violence, the implementation must still prioritize the protection of victims according to Law Number 23 of 2004. Restorative justice can only be implemented if there is an agreement, there is no serious violence, and there is a guarantee that the act will not be repeated. Challenges in implementing restorative justice in cases of domestic violence include lack of regulation, understanding of officers, and resistance from the parties. Solutions include strengthening internal regulations, training officers, SOPs that side with victims, and involvement of suport institutions. The government and society must jointly suport regulation, education, and supervision so that justice for victims is guaranteed.